Metody a přístupy v prevenci rizikových činitelů na prvním stupni základních škol - Hanousková, Miloslava (Jihočeská univerzita, 2007)
The theoretical part of the Master's Thesis devoted to risk factors that can change into dystropy of children in the infantry school. Further, I have processed methods related to this problems and mentioned approaches that can be alternatively used in preventive activities. This includes not only activities concentrated on children and youth, but also approaches towards teachers, parents and general public. I always tried to emphasize what is the most effective for the school environment. Illustrating examples are also included.
Methods and approaches in prevention of risk factors in the first degree of basic schools
Keywords: První stupeň základních škol; žáci; učitelé; primární prevence; rizikoví činitelé; poruchy chování a emotivity; metodika; přístupy; First degree of basic schools; pupils; teachers; primary prevention; risk factors; bebehavioral disturbance and emotivity; methology; approaches